2004
DOI: 10.1038/sj.mp.4001579
|View full text |Cite
|
Sign up to set email alerts
|

MR-based in vivo hippocampal volumetrics: 2. Findings in neuropsychiatric disorders

Abstract: Magnetic resonance imaging (MRI) has opened a new window to the brain. Measuring hippocampal volume with MRI has provided important information about several neuropsychiatric disorders. We reviewed the literature and selected all English-language, human subject, data-driven papers on hippocampal volumetry, yielding a database of 423 records. Smaller hippocampal volumes have been reported in epilepsy, Alzheimer's disease, dementia, mild cognitive impairment, the aged, traumatic brain injury, cardiac arrest, Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
243
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(255 citation statements)
references
References 439 publications
(357 reference statements)
8
243
0
4
Order By: Relevance
“…In the same study, no comparable differences could be demonstrated between MZ twins concordant for high anxiety/depression (7 pairs) relative to MZ twins concordant for low anxiety/depression (15 pairs) (de Geus et al, 2007). A possible mechanism for hippocampal tissue loss is exposure to repeated episodes of hypercortisolemia (Geuze et al, 2005). Nevertheless, we did not find any correlations between clinical variables and hippocampus volume nor did the high-risk MZ and DZ twins differ from each other on any of the clinical variables.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the same study, no comparable differences could be demonstrated between MZ twins concordant for high anxiety/depression (7 pairs) relative to MZ twins concordant for low anxiety/depression (15 pairs) (de Geus et al, 2007). A possible mechanism for hippocampal tissue loss is exposure to repeated episodes of hypercortisolemia (Geuze et al, 2005). Nevertheless, we did not find any correlations between clinical variables and hippocampus volume nor did the high-risk MZ and DZ twins differ from each other on any of the clinical variables.…”
Section: Discussionmentioning
confidence: 88%
“…However, recent observations of hippocampal volume reductions in drug-naïve first-episode depressed subjects (Frodl et al, 2002;Kronmuller et al, 2009;MacMaster et al, 2008;Zou et al, 2009), suggest that the hippocampus might already be affected early in the disease, independent of chronicity, number of relapses, and medication. Nevertheless, hippocampal volume reductions are likely not specific to unipolar depression and have been reported in several neuropsychiatric disorders (Geuze et al, 2005). Notably, the hippocampus has been found reduced in schizophrenia patients in different stages of the disease as well as in their unaffected relatives (Ebdrup et al, 2010;Lawrie et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it is unlikely that these findings are specific to schizophrenia (Geuze et al, 2005). A major limitation of our study is the relatively small sample size with the consequence that we may be unable to detect small group differences because of limited statistical power.…”
Section: Arms-nt)mentioning
confidence: 88%
“…Most biomarkers currently suffer from poor reproducibility across laboratories (Mattson et al, 2010;Frisoni and Jack, 2011). In the case of hippocampal volume, despite high intra-laboratory reproducibility, normal hippocampal volume figures can vary 2.5-fold (Geuze et al, 2005). This has so far prevented the definition of universally accepted norms and individually applicable normality thresholds.…”
Section: Limiting Factors For Widespread Use In the Clinicmentioning
confidence: 99%